2000
DOI: 10.1016/s0016-7185(00)00016-6
|View full text |Cite
|
Sign up to set email alerts
|

Globalisation, information technology and the emergence of niche transnational cities: the growth of the call centre sector in Dublin

Abstract: The development of information and communications technologies (ICT) has facilitated the emergence of a complex global urban system in which many formerly lower-order cities have been carving out``niche'' specialist functions serving urban ®elds of transnational dimension. This is illustrated in the case of Dublin, which in recent years has been transcending its traditional role as IrelandÕs national metropolis through the development of a range of functions servicing mainly European markets. One such function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 24 publications
0
46
1
2
Order By: Relevance
“…Certainly, the existing literature provides useful insights into the growth of internationally traded services in Ireland (BREATHNACH, 2000;GRIMES, 2003;GRIMES and WHITE, 2005), some of which may be part of larger manufacturing or software-producing corporations. However, the present study represents the first attempt to examine service-specific KIBS firms while focusing on their locational pattern within the Greater Dublin region.…”
Section: Dublin: Towards An Informational City?mentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, the existing literature provides useful insights into the growth of internationally traded services in Ireland (BREATHNACH, 2000;GRIMES, 2003;GRIMES and WHITE, 2005), some of which may be part of larger manufacturing or software-producing corporations. However, the present study represents the first attempt to examine service-specific KIBS firms while focusing on their locational pattern within the Greater Dublin region.…”
Section: Dublin: Towards An Informational City?mentioning
confidence: 99%
“…The increasing linkages with the global economy have recently led researchers from the Globalization and World Cities Study Group and Network (GaWC) to label Dublin an 'emerging global city ' (TAYLOR et al, 2002, p. 100). Secondly, it could be argued that hand-in-hand with its globalization, Dublin experienced unprecedented economic growth, part of which was a significant expansion of internationally traded services (BREATHNACH, 2000;GRIMES, 2003;GRIMES and WHITE, 2005) and knowledge-intensive business services (KIBS). Importantly, CASTELLS (1989) and HALL and PAIN (2006) alike see KIBS as the major driving force behind the emergence of the 'multinuclear' or 'polycentric' spatial structures.…”
Section: Introductionmentioning
confidence: 99%
“…However, drawing on Manuel Castells' (1996) argument that the global city is a process, not a place, it is becoming evident that regional and local urban centers become integrated into a global network through both economic and non-economic functions. This idea has been reinforced by studies such as that of Breathnach (2000), who demonstrated that lower order urban centers like Dublin, Ireland, gained global prominence as they developed new transnational niche functions. The same is also true of cities like Bangalore and Hyderabad, with their increasing recognition as global centers of the IT industry.…”
Section: World Cities Globalization and Transnationalismmentioning
confidence: 99%
“…While in the front stage customer contact is high and active, it brings about unavoidable inefficiencies, and the human relation skills become a dominant factor in designing the process [6]. Study [8] adds that moving some of the back-stage functions from developed areas (or even countries) to underdeveloped regions may increase greatly efficiency because of the reduction in labor costs and taxation.…”
Section: Decoupling For Efficiencymentioning
confidence: 99%